Le discriminazioni di genere nell’accesso a beni e servizi sanitari. Ovvero delle tensioni irrisolte del diritto antidiscriminatorio (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The paper analyses gender antidiscrimination legislation regarding access and supply of goods and services in health. The paper focuses on the evolution of EU legislation prohibiting discrimination based on gender, “race” and ethnic origins, sexual orientation, disability, age, religion and personal convictions. By framing these issues, the paper addresses the complex relationship between EU antidiscrimination principle and the Constitutional principle of equality in the perspective of the Antisubordination dimension, trying to outline the limits of antidiscrimination legislation.
Keywords: Antidiscrimination; equality; antisubordination; health goods and services; gender